Cytotoxicity of and DNA adduct formation by ellipticine in human U87MG glioblastoma cancer cells - Martinkova, Eva; Dontenwill, Monique; Frei, Eva; Stiborova, Marie (Neuro endocrinology letters, 2009)
OBJECTIVES: Ellipticine is a potent antineoplastic agent exhibiting multiple mechanisms of action with promising brain tumor specificity. This anticancer agent should be considered a pro-drug, whose pharmacological efficiency and/or genotoxic side effects are dependent on its cytochrome P450 (CYP) - and/or peroxidase-mediated activation to species forming covalent DNA adducts. Ellipticine can also act as an inhibitor or inducer of biotransformation enzymes, thereby modulating its own metabolism leading to its genotoxic and pharmacological effects. The toxicity of ellipticine to U87MG glioblastoma cells and mechanisms of its action to these cells are aims of this study. METHODS: Ellipticine metabolites formed in U87MG cells were analyzed using HPLC. Covalent DNA modifications by ellipticine were detected by 32P-postlabeling. CYP enzyme expression was examined by QPCR and Western blot. RESULTS: U87MG glioblastoma cell proliferation was efficiently inhibited by ellipticine. This effect might be associated with formation of two covalent ellipticine-derived DNA adducts, identical to those formed by 13-hydroxy- and 12-hydroxyellipticine, the ellipticine metabolites generated by CYP1A1, 1B1 and 3A4, lactoperoxidase and cyclooxygenase 1, the enzymes expressed in U87MG cells. Moreover, by inducing CYP1B1, 3A4 and 1A1 enzymes in U87MG cells, ellipticine increases its own enzymatic activation, thereby enhancing its own genotoxic and pharmacological potential in these cells. Ellipticine concentration used for U87MG cell treatment is extremely important for its pharmacological effects, as its metabolite profiles differed substantially predicting ellipticine to be either detoxified or activated. CONCLUSION: The results found in this study are the first report showing cytotoxicity and DNA adduct formation by ellipticine in glioblastomas.
Keywords: Ellipticines; Cell Proliferation; Cytochrome P-450 Enzyme System; Glioblastoma; nádorové buněčné linie; Cell Line, Tumor; lidé; adukty DNA; western blotting; glioblastom; Humans; systém (enzymů) cytochromů P-450; Phosphorus Radioisotopes; elipticiny; proliferace buněk; viabilita buněk; Dose-Response Relationship, Drug; protinádorové látky; Antineoplastic Agents; DNA Adducts; polymerázová řetězová reakce; vysokoúčinná kapalinová chromatografie; Polymerase Chain Reaction; messenger RNA; vztah mezi dávkou a účinkem léčiva; Cell Survival; Autoradiography; Chromatography, High Pressure Liquid; radioizotopy fosforu; Blotting, Western; autoradiografie; RNA, Messenger